SP-A and SP-D: Dual Functioning Immune Molecules With Antiviral and Immunomodulatory Properties - Watson, Alastair; Madsen, Jens; Clark, Howard William (Frontiers in Immunology, 2021)
Surfactant proteins A (SP-A) and D (SP-D) are soluble innate immune molecules which maintain lung homeostasis through their dual roles as anti-infectious and immunomodulatory agents. SP-A and SP-D bind numerous viruses including influenza A virus, respiratory syncytial virus (RSV) and human immunodeficiency virus (HIV), enhancing their clearance from mucosal points of entry and modulating the inflammatory response. They also have diverse roles in mediating innate and adaptive cell functions and in clearing apoptotic cells, allergens and other noxious particles. We summarize here how the properties of these first line defense molecules modulate inflammatory responses, as well as host-mediated immunopathology in response to viral infections. Since SP-A and SP-D are known to offer protection from viral and other infections, if their levels are decreased in some disease states as they are in severe asthma and chronic obstructive pulmonary disease (COPD), this may confer an increased risk of viral infection and exacerbations of disease. Recombinant molecules of SP-A and SP-D could be useful in both blocking respiratory viral infection whilst also modulating the immune system to prevent excessive inflammatory responses seen in, for example, RSV or coronavirus disease 2019 (COVID-19). SP-A and SP-D could have therapeutic potential in neutralizing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus and modulating the inflammation-mediated pathology associated with COVID-19. Further work investigating the potential therapeutic role of SP-A and SP-D in COVID-19 and other infectious and inflammatory diseases is indicated.